Molecular Identification and Genetic Characterization of Macrophomina phaseolina Strains Causing Pathogenicity on Sunflower and Chickpea - Khan, Ali N.; Shair, Faluk; Malik, Kamran; Hayat, Zafar; Khan, Muhammad Ayub; Hafeez, Fauzia Yusuf; Hassan, Muhammad Nadeem (Frontiers in Microbiology, 2017)
Macrophomina phaseolina is the most devastating pathogen which cause charcoal rot and root rot disease in various economically important crops. Three strains M. Phaseolina1156, M. Phaseolina1160 and M. Phaseolina PCMC/F1 were tested for their virulence on sunflower (Helianthus annuus L.) and chickpea (Cicer arietinum L).The strains showed high virulence on both hosts with a disease score of 2 on chickpea and sunflower. The strains also increased the hydrogen per oxide (H2O2) content by 1.4-1.6 fold in root as well as shoot of chickpea and sunflower. A significant increase in antioxidant enzymes was observed in fungal infected plants which indicated prevelance of oxidative stress during pathogen propagation. The M. phaseolina strains also produced hydrolytic enzymes such as lipase, amylase and protease with solubilization zone of 5-43mm, 5-45mm and 12-35 mm respectively. The M. Phaseolina strains were identified by 18S rRNA and analyzed for genetic diversity by using random amplified polymorphic DNA (RAPD) markers. The findings based on RAPD markers and 18S rRNA sequence analysis clearly indicate genetic variation among the strains collected from different hosts. The genetically diverse strains were found to be pathogenic to sunflower and chickpea.